1995
DOI: 10.1042/bj3060077
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of non-conjugated olefinic substrate analogues with dopamine β-monooxygenase: catalysis and mechanism-based inhibition

Abstract: The reaction of dopamine beta-monooxygenase (DBM; EC 1.14.17.1) with the prototypical non-conjugated olefinic substrate, 2-(1-cyclohexenyl)ethylamine (CyHEA) [see Sirimanne and May (1988) J. Am. Chem. Soc. 110, 7560-7561], was characterized. CyHEA undergoes facile DBM-catalysed allylic hydroxylation to form (R)-2-amino-1-(1-cyclohexenyl)ethanol (CyHEA-OH) without detectable epoxidation or allylic hydroxylation to form (R)-2-amino-1-(1-cyclohexenyl)ethanol (CyHEA-OH) without detectable epoxidation or allylic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…Oxidation of CGA residues has previously been described [61]. In chromaffin granules, for instance, MS analysis has revealed oxidation at methionine residues, which may be related to a redox mechanism inside the granules [63].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidation of CGA residues has previously been described [61]. In chromaffin granules, for instance, MS analysis has revealed oxidation at methionine residues, which may be related to a redox mechanism inside the granules [63].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, in the isolated working heart of the frog Rana esculenta, the concentration-dependent negative inotropism and inhibition of the b-adrenergicdependent positive inotropy elicited by the N-terminal domain of CGA [i.e. human recombinant vasostatin I and bovine CGA(7-57)], as well as by the synthetic peptides corresponding to frog and bovine CGA(4-16), CGA (47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66), and bovine CGA(1- 40), have been analysed in details [32]. More recently, using the Langendorff-perfused rat heart model, we have reported that the two recombinant human vasostatins STA-CGA(1-76) (vasostatin I) and STA-CGA(1-113) (vasostatin II) display similar negative inotropic effects and antagonize the b-adrenergic-dependent positive inotropism, the latter being counteracted by vasostatin I in a noncompetitive type of antagonism [33].…”
mentioning
confidence: 99%
“…Other olefinic inactivators of PHM include monoethyl fumarate 25 , styrylthioa-cetate 38 , 2- and 3-alkenoates 32 , vinylglycine 32 , 3-substituted acrylates 32 , substituted 4-oxo-2-hexenoates 30 , and D-Phe-L-Phe-L-vinylglycine 64 . Other monooxygenases, P 450 and dopamine β-monooxygenase (DβM, structurally and mechanistically related to PHM), are inactivated by olefins 65–68 . Most of these olefinic inactivators exhibit characteristics of suicide substrates: the inactivation only occurs during enzyme turnover and substrates or competitive inhibitors protect the monooxygenases against inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Copper-free PHM is catalytically inactive 53,62,78 . Cinnamates are known to form complexes with both Cu(I) 79,80 and Cu(II) 81 and copper removal/chelation has been attributed to specific PHM 61 and DβM inhibitors 68 . PHM inactivation requires turnover; thus, inactivation of PHM by cinnamate could result from the formation of a relatively high affinity cinnamate–Cu(I) complex.…”
Section: Discussionmentioning
confidence: 99%
“…Further work has revealed that this enzyme is able to exhibit a broad specificity towards its organic substrate. Many other molecules, in addition to dopamine, have been shown to succumb to its catalytic activity [62][63][64][65][66][67][68][69][70][71][72].…”
Section: Closing the Dividementioning
confidence: 99%